Glucose oxidase effect on treatment of textile effluent containing reactive azo dyes by Phanerochaete chrysosporium. Issue 7 (19th January 2017) - Ansari, Zahra; Karimi, Afzal; Sedghi, Shahram; Razzaghi, Mohammad; Ebrahimi, Sirous
Abstract: BACKGROUND: Chemically different types of dyes have been proven to be degraded by peroxidases of Phanerochaete chrysosporium . Hydrogen peroxide is required as a co‐substrate for peroxidases during the oxidation process. RESULTS: Investigating the effect of glucose oxidase (GOx) (EC 1.1.3.4) on treatment of textile effluent containing recalcitrant diazo and azo dyes by P. chrysosporium was the main aim of this research. The effects of glucose, GOx and Mn 2+ on chemical oxygen demand (COD), decolorization and manganese peroxidase (MnP) activity were evaluated in repeated batch operations. At the end of the fifth batch, the decolorization efficiency increased 4.18‐fold compared with reference batches (i.e. no additive received batches). An increase in MnP activity and COD removal percentage by 4.5‐ and 5‐fold, respectively, were observed when introducing GOx+glucose. CONCLUSION: In vivo addition of GOx+glucose could increase the decolorization efficiency of real sample effluent not only by providing H2 O2 for catalytic activity of peroxidases but also by providing gluconic acid, favoring the pH of the medium and increasing peroxidase activity as well. Also, these findings may be useful for discerning the role of manganese ions and oxidases of fungi as well as their interaction in the decolorization process. © 2016 Society of Chemical Industry